TEACHER'S SCIENTIFIC OUTLOOK AND PEDAGOGICAL ERUDITION - A GUARANTEE OF EFFECTIVE EDUCATION (Universal International Scientific Journal, 2026)
The article analyzes the impact of a teacher's scientific worldview and pedagogical erudition on educational effectiveness in the modern education system. Scientific worldview is the methodological basis of the educational process, and pedagogical erudition serves to develop the teacher's professional skills. These two factors form the ability to think independently in students.
Keywords: pedagogical erudition, scientific worldview, educational effectiveness, pedagogical skills, teacher competence, quality of education.